The role of family support and HIV/AIDS stigma on adherence and non-adherence to antiretrovirals at Nzhelele in Limpopo Province, South Africa - Mathivha, Tshifularo Maud (University of Limpopo (Turfloop Campus), 2012)
Objectives: To determine the level of adherence of people who are on ARVs and to determine the influence of HIV and AIDS stigma and family support on adherence and non-adherence to antiretrovirals. Methods: A descriptive cross sectional study involving 175 HIV/AIDS adult patients attending Siloam hospital was conducted. These patients were on ARV drugs. They were investigated for the level of adherence and the influence of HIV and AIDS stigma and family support on adherence and non-adherence to antiretrovirals. Data were collected from respondents through self-administered questionnaires which were distributed to 175 randomly selected participants. The key variables were demographic information and social support and disclosure, current use of ARVs and personal experience of living with HIV/AIDS. Data were analyzed using descriptive statistics, numerical summaries, tables, graphs, ANOVA, Pearson chi-square test and statistical package for social sciences (SPSS). Results: Forty comma eight percent (40,8%) of the respondents on ARVs were males and 28, 8 % females aged between 23-35 years; 23, 9% males and 40, 4% females ranged between 36-45 years; 35, 2% males and 30, 8% were 46 years old and above. The most commonly cited reasons for missing doses were: Social grant, forgetting, side effects and stigma. The most cited reasons for taking medication were: respondents wanted to feel better; to increase the CD4 count; and they feared death. The majority of the adhering participants, 68, 9% and 55, 8% of the non- adhering group never experienced negative reactions from their families after disclosure. There was no significant difference between the adhering and the non adhering group (P =0.250). A substantial number of ARV users of the adhering group 92, 2% participants disclosed that they were receiving support which included emotional/psychological support, financial support, physical care support as well as reminders to ensure that they took their medications on time. There was no significant difference between the adhering and the non adhering group on the general satisfaction with the overall support they received from their family (p= 0.976). Conclusion: Patients have a range of reasons for failing to adhere to their antiretroviral therapy and reasons for adhering. Support can improve adherence to therapy and patients can only receive support if they revealed their HIV positive status. It was recommended that the community should be sensitised about the availability of treatment and the importance of adherence Keywords: Adherence, antiretrovirals, HIV/AIDS, stigma and family support
Thesis (M.PH.) --University of Limpopo, 2012
Keywords: Family support; HIV/AIDS; Stigma; Antiretrovirals; 362.1969792; Patient compliance; AIDS (Disease) -- Patients; Clinical psychology